2018
DOI: 10.26719/2018.24.8.729
|View full text |Cite
|
Sign up to set email alerts
|

Adapting life to the reality of diabetes

Abstract: Study design and participants This was a qualitative study using a grounded theory approach. Grounded theory is especially suitable for analysing social processes, as it rises above merely describing a topic, and instead facilitates a deeper understanding without losing parts and details (12). Following approval (No. 900603) by the Ethics Committee of the Mashhad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies have found that parents of children with T1D felt the disease affected the diet and social activities of the entire family, and they considered their adapted life with the disease as the ‘new normal’ (Campbell et al, 2014; Howe et al, 2012; Symons et al, 2015). Adaptation to diabetes involves a dynamic process of disease management, during which patients adjust their perception, emotions and behaviours to reconstruct a ‘normal life’ (Areshtanab et al, 2018). After their children were diagnosed, the parents who participated in this study assisted their children in rebuilding a healthy life, ultimately accepting their children's diagnosis and regarding disease management as a part of daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that parents of children with T1D felt the disease affected the diet and social activities of the entire family, and they considered their adapted life with the disease as the ‘new normal’ (Campbell et al, 2014; Howe et al, 2012; Symons et al, 2015). Adaptation to diabetes involves a dynamic process of disease management, during which patients adjust their perception, emotions and behaviours to reconstruct a ‘normal life’ (Areshtanab et al, 2018). After their children were diagnosed, the parents who participated in this study assisted their children in rebuilding a healthy life, ultimately accepting their children's diagnosis and regarding disease management as a part of daily life.…”
Section: Discussionmentioning
confidence: 99%